Tindakan Bullying di Media Sosial; Komparasi Hukum Pidana Islam dan Undang-Undang Nomor 19 Tahun 2016 Tentang ITE - Hasriani Hasir; Sohrah Sohrah (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab dan Hukum, 2021)
The focus of this study: (1) How to form acts of bullying on social media. (2) What is the view of Islamic Law towards acts of bullying on social media. (3) How to sanction acts of bullying in social media according to Law No.19 of 2016 concerning Information and Electronic Transactions. This type of research is a type of literature research, the method used is to use normative theological approach (Islamic Law), normative juridical approach (Law), sociological approach, and comparative approach(comparison). The data sources used are primary data sources, secondary data sources, and tertiary data sources. The data used comes from the prevailing laws and regulations, both from Islamic law and positive law. Cyber Bullying is an act of humiliation, intimidation, psychic violence committed by a person, group or institution through social media against people, groups or other institutions. Sometimes the perpetrator of bullying also makes the victim helpless and can even take the victim's life. The regulation of Bullying Act is stipulated in Law No. 19 of 2016 to ensnare the perpetrators.  Although the description of the word Cyber bullying itself has not set about Cyber Bullying and only a few parts that include the type of Cyber Bullying that is, defamation, threats / intimidation, fake news, slander, spreading hatred and hostility. In Islamic Law the act of Cyber Bullying is very clearly prohibited because it includes mistreating or hurting others. Which is not in accordance with the guidance of Syara' that Islam is a religion that highly upholds the honor for each uamtnya, but for the sanctions have not been specifically in nash but the crime of Cyber Bullying is included in the realm of Jarimah Ta'zir